Ocular complications of radiotherapy – the literature overview - Filarska, Dorota; Czyżewska, Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2000)
The aim of this review study is to present ocular complications after radiotherapy. The adverse effects of radiation such as: cataract formation, dry-eye syndrome, radiation retinopathy, optic nerve injuries, osteogenic sarcoma are described. According to literature data revieved, main risk factors of radiotherapy-induced ocular complications include: radiation dose, other disease, some drugs, patient age. In majority of cases there is no effective treatment of this effects of radiation therapy.